The Influence of Chemical Change on Protein Dynamics: A Case Study with Pyruvate Formate-Lyase - Hanzevacki, Marko; Čondić-Jurkić, Karmen; Banhatti, Radha Dilip; Smith, Ana-Suncana; Smith, David M. (Chemistry - A European Journal, 2019)
Pyruvate formate-lyase (PFL) catalyzes the reversible conversion of pyruvate and coenzyme A (CoA) into formate and acetyl-CoA in two half-reactions. For the second half-reaction to take place, the S−H group of CoA must enter the active site of the enzyme to retrieve a protein-bound acetyl group. However, CoA is bound at the protein surface, whereas the active site is buried in the protein interior, some 20–30 Å away. The PFL system was therefore subjected to a series of extensive molecular dynamics simulations (in the μs range) and a host of advanced analysis procedures. Models representing PFL before and after the first half-reaction were used to examine the possible effect of enzyme acetylation. All simulated structures were found to be relatively stable compared to the initial crystal structure. Although the adenine portion of CoA remained predominantly bound at the protein surface, the binding of the S−H group was significantly more labile. A potential entry channel for CoA, which would allow the S−H group to reach the active site, was identified and characterized. The channel was found to be associated with accentuated fluctuations and a higher probability of being in an open state in acetylated systems. This result suggests that the acetylation of the enzyme assumes a prominent functional role, whereby the formation of the acyl intermediate serves to initiate a subtle signaling cascade that influences the protein dynamics and facilitates the entry of the second substrate.
CRIS-Team Scopus Importer:2019-05-24
Keywords: coenzyme A; molecular dynamics; protein dynamics; pyruvate formate-lyase; radical enzymes